STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN JUMLAH PENGUNJUNG KARAOKE KELUARGA INUL VIZTA PEKANBARU - Saputra, Anggia Tri; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Karaoke is the place for expressing vocal emphasis in singing, the priority of karaoke place is privacy for singing. Customers can sing (karaoke) in a closed room only with family or friends. The songs are sung can be selected in according selection of the family because it has a thousands collection of karaoke songs from the Oldest to newest. The background of this study aims to determine What forms of marketing communication strategies Inul Vizta in increasing the number of visitors to What factors supporting marketing communication strategy for increasing the number of visitors in karaoke Inul Vizta PekanbaruThis study will be held in Inul Vizta Pekanbaru at Jalan Soekarno - Hatta, Pekanbaru, Riau. The study will use a purposive sampling technique (purposive sampling), this technique include those who are selected on the basis of certain criteria which made from researchers based on the object. Where those the population who don’t fit the criteria are not sampled. The Informans in this study are 5 people, that consist of 1 leader and 2 employees of Inul Vizta Pekanbaru and then 2 visitors of Inul Vizta.The strategy of marketing communication that do in karaoke Inul Vizta in increasing the number of visitors through advertising, sales promotion, personal selling, publicity, direct marketing. From the marketing communication strategy that executed in the from has not run optimally. Karaoke Inul Vizta Pekanbaru has employees with the education and best work experience, the location is strategic vista inul karaoke, means and complete facilities as supporting factor. The inhibiting factors of marketing communication strategy in karaoke Inul Vizta pekanbaru is less advertising and the promotionsKeywords: communication strategy, marketing strategy, marketing communication strategy, factors inhibiting and supporting, inul vizta